Editorial - Wren Bareiss (Qualitative Research in Medicine & Healthcare, 2021)
In her final editorial for Qualitative Research in Medicine and Healthcare, Mariaelena Bartesaghi described how her health condition prevented her from continuing as Editor-in-Chief. Dr. Bartesaghi described herself as a character in the type of stories that we research and report about in this very journal. Like so many people whose stories have been told and reflected upon in QRMH since Dr. Bartesaghi founded the journal in 2017, her story “is one about the burdens of being a patient as well as a human being who suffers” (p. vi). [...]